Thoracic Block Technique Associated with Positive End-Expiratory Pressure in Reversing Atelectasis - Luciana Carnevalli Pereira; Ana Paula de Souza Netto; Fernanda Cordeiro da Silva; Silvana Alves Pereira; Cristiane Aparecida Moran (Case Reports in Pediatrics)
A preschool four-year-old male patient had been admitted to the Mandaqui Hospital with a diagnosis of lobar pneumonia, pleural effusion, and right lung atelectasis. Treatment consisted of antibiotics and physiotherapy sessions, using a technique described in the literature as Insufflation Technique to Reverse Atelectasis (ITRA), which consists of a thoracic block of healthy lung tissue, leaving only the atelectasis area free, associated with the use of invasive or noninvasive mechanical ventilation with positive airway pressure for reversal of atelectasis. Two physiotherapy sessions were conducted daily. The sessions lasted 20 minutes and were fractionated into four series of five minutes each. Each series bilateral thoracic block was performed for 20 seconds with a pause lasting for the same time. Associated with the thoracic block, a continuous positive airways pressure was used using a facial mask and 7 cm H2O PEEP provided via CPAP. Conclusion. ITRA technique was effective in reversing atelectasis in this patient.